PENGARUH RELATIONSHIP MARKETING, KEUNGGULAN BERSAING DAN IMPLEMENTASI ISTISHNA’ TERHADAP LOYALITAS KONSUMEN ANUGERAH BETON - Rina Indah Maysaroh; Agus Eko Sujianto (JURNAL ILMIAH EDUNOMIKA, 2022)
This research aimed to validate the effect of relationship marketing, competitive advantage, and the implementation of istishna’s contracts on consumer loyalty. The approach in this research used quantitative and data collection methods by distributing questionnaires and supporting data collected through documentation techniques. Respondents from this study were 50 business consumers of Anugerah Beton. This research was an analytical technique using validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, F-test, T-test, and the coefficient of determination. The results of this research indicated that the test material data can be said to be valid and can be proven by testing the validity. The conclusion from the calculation of the data was that there was a significant positive between the relationship marketing variable (x1) and competitive advantage (x2) on the consumer loyalty variable (y). However, there was an insignificant positive between istishna’s contract implementation variables (x3) on the consumer loyalty variable (y). This was proved by the multiple linear regression test and T-test. The results showed that relationship marketing and competitive advantage can be used to establish and maintain customer loyalty.